2006
DOI: 10.1243/09576509jpe202
|View full text |Cite
|
Sign up to set email alerts
|

Development of the free piston expander for work recovery in transcritical CO2 refrigeration cycle

Abstract: Replacing the throttle valve with an expander is beneficial to the performance improvement on the transcritical CO 2 refrigeration cycle. The expander is hereby developed for this purpose in this paper. With the required working conditions, performance potential, reliability, etc. considered, the free piston machine is selected as the most suitable concept after a comparison among some candidates. The single acting structure is adopted, in which an auxiliary compressor is arranged on a common shaft to utilize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Peng et al. 3 developed a free piston expander coupled with an auxiliary compressor to consume the recovered work for transcritical CO 2 refrigeration cycle, the feasibility of the prototype was validated through compressed air and CO 2 . Nickl et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al. 3 developed a free piston expander coupled with an auxiliary compressor to consume the recovered work for transcritical CO 2 refrigeration cycle, the feasibility of the prototype was validated through compressed air and CO 2 . Nickl et al.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the expander without modifying the geometric parameters of the original compressor performed better than the modified one, and the maximum recorded volumetric efficiency and isentropic efficiency were 68% and 42%, respectively. Peng et al 3 developed a free piston expander coupled with an auxiliary compressor to consume the recovered work for transcritical CO 2 refrigeration cycle, the feasibility of the prototype was validated through compressed air and CO 2 . Nickl et al 4 have developed three generations of piston expander-compressor unit for CO 2 refrigeration systems since 1994.…”
Section: Introductionmentioning
confidence: 99%
“…However, the complexity of components-especially the control mechanism-puts it at a disadvantage in the area of domestic refrigeration systems. Although a free-piston expander with simple active inlet/outlet control is promising for application in the transcritical CO 2 cycle (Peng et al 2006), the volumetric expansion ratio of HCFCs/HFCs is larger than that of CO 2 and, thus, the expander is enlarged. A screw expander has the function of energy recovery in the refrigeration system, but the requirement of high precision in fabrication and high cost make this expander less attractive for use in domestic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, some of the compressor designs which are available have been modified to be used as expanders. For example, the reciprocating piston [65][66][67][68][69][70], rotary vane [71,72], rolling piston [73][74][75][76], revolving vane [56,[77][78][79][80], screw [81][82][83][84][85] and scroll [86][87][88][89][90][91] have all been modified to be used as expanders.…”
Section: Evolution Of Refrigerantsmentioning
confidence: 99%
“…This is not common for compressors that usually avoid wet compression because the presence of liquid droplets can damage the compressor [93]. Secondly, some expander types (e.g., reciprocating piston, rolling piston and revolving vane) require externally controlled valves such as solenoid valves [65], electronically activated valves [5] or mechanically activated valves [67,74,94] at the inlet to control the beginning and ending of the suction process. And lastly, expanders must be able to handle sealing, lubrication, liquid slugging, cavitation, vibration and noise control problems which may affect the performance of the expander [95].…”
Section: Expanders In Air-conditioning Heating and Other Applicationsmentioning
confidence: 99%